Education About the Importance of Attention Nutritional Needs in Children - Asla Amellia Harris; Asep Bayu Dani Nandiyanto (Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to help educate and provide an understanding of the importance of paying attention to the nutritional needs of children, so children's growth and development can develop healthily and have adequate nutritional balance in children's bodies from an early age. Paying attention to nutrition in children from an early age has indeed become a responsibility for every parent. The method used is descriptive qualitative research and uses a questionnaire as one of the media used to determine the knowledge of the target respondents. Therefore, the results of this research are 7 parents who participated as respondents showed that they knew the information required in the questionnaire. 11 fifth-grade students, on the other hand, displayed a lack of fundamental understanding and familiarity with the subject. Thus, with this research, it can increases students and parents understanding about the importance of nutritional needs of children and the awareness in considering what intake should be given to children so that children’s continue to get balanced nutrition.